Some Comparative Studies Using 99mTc and 131I in Thyroid Scanning - Górowski, T.; Chomicki, O. A. (Nuklearmedizin - NuclearMedicine, 1976)
By comparing thyroid scans made with 99mTc and 131I in 40 euthyroid goiter patients large discrepancies were found in 20% of all cases. For example, “warm” nodules on 99mTc scans were found to be “cold” on 131I scans, or a “cold” nodule on a 99mTc scan was observed as a “warm” one on a 131I scan. The above discrepancies seem to result from the differences in the metabolism of the two radioisotopes in the thyroid and those in the time which elapsed between the administration of the radioisotope and the execution of the scan.Generally speaking 99mTc thyroid scintigraphy should not be recommended as a routine technique in adults, its usefulness being limited to the cases in which 131I scans were found to be illegible. “Cold” nodules on 99mTc scans should also be reexamined after T3 stimulation.